Paediatric endocrinology and diabetes - Butler, Gary (Gary E.); Kirk, Jeremy, Dr (Oxford : Oxford University Press, 2020)
This handbook covers anatomy and physiology before moving on to identification, investigation and management of specific endocrine disorders. As well as covering common and less common endocrine problems, there are also chapters on endocrine investigations and endocrine emergencies, designed for quick reference.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 3, 2020).
Keywords: Pediatric endocrinology; Diabetes in children